G353 Impact of Echocardiogram in the assessment of babies with chronic lung disease. (7th April 2014) - Abraham, D; Yajamanyam, PK; Rasiah, SV
Abstract : Background: Chronic lung disease (CLD) defined as oxygen requirement at 36 weeks corrected gestational age (CGA) is a significant neonatal morbidity. Pulmonary hypertension (PH) is a recognized complication of CLD and is associated with significant mortality. 1 Objectives: To determine the incidence of PH in preterm infants bor2 weeks gestation (GA) diagnosed with CLD. To evaluate the impact of the use of echocardiography as an assessment tool to detect PH in CLD. Methods: Echocardiography was performed at approximately 36 weeks CGA on 52 preterm infants with CLD as part of routine clinical care. Echocardiography findings and respiratory outcomes at discharge were retrospectively collected for these infants born between January 2011 and December 2012. Results: The median GA at birth was 25wk (25–27) and median birth weight 785 g (610–895). 3 infants (all needing non-invasive positive airway pressure at 36wk CGA) were found to have significant PH and subsequently died. 31 infants had a normal echocardiogram. 5 infants needed referral to paediatric cardiology services for other cardiac abnormalities (dysplastic pulmonary valve, ventricular septal defect and atrial septal defect). An additional 12 infants had persistent patent ductus arteriosus (PDA). Four infants had evidence of ventricular hypertrophy (all receiving steroids for their CLD). 13 infants requiring low flow nasal cannula oxygen at 36wk CGA had no signs of PH on echocardiography and all were discharged from the neonatal unit without needing home oxygen. Conclusions: The incidence of PH in this cohort is approximately 6%, which is less than previously reported. 1, 2 In addition we found that 40% of infants in this cohort had other significant findings on echocardiography requiring follow up. Infants requiring low flow nasal cannula oxygen at 36wk CGA had the best prognosis and showed no evidence of PH on echocardiography. Our results suggest that echocardiography is an important adjunct to clinical assessment of infants with CLD. References: Berkelhamer SK, Mestan KK, Steinhorn RH. Pulmonary hypertension in bronchopulmonary dysplasia. Semin Perinatol. 2013;37(2):124–31. Bhat R, Salas AA, Foster C, Carlo WA, Ambalavanan N. Prospective analysis of pulmonary hypertension in extremely low birth weight infants. Pediatrics. 2012;129(3):e682-9.